Unit-length, single-stranded circular DNAs of both polarity of begomoviruses are generated in Escherichia coli harboring phage M13-cloned begomovirus genome with single copy of replication origin - Wu, Chia-Ying; Yang, Su-Hua; Lai, Yi-Chin; Lin, Na-Sheng; Hsu, Yau-Heiu; Hu, Chung-Chi (Virus research, 2007)
Replication of genomic DNAs of plant-pathogenic begomoviruses has been demonstrated in prokaryotes, which supported the possibility of analyzing DNA replication process of begomoviruses in bacteria. However, previous studies indicated that the replication of begomovirus DNAs in prokaryotes requires tandem constructs of viral genomes with at least two copies of the origin of replication ( ori). In this study, phage M13 vector harboring the unit-length genome with only a single copy of ori of a mono-partite begomovirus, Ageratum yellow vein virus PD isolate (AYVV-[PD]), was constructed and used to investigate the replication of AYVV-[PD] DNAs in Escherichia coli. The generation of single-stranded, circular DNAs (sscDNAs) corresponding to the unit-length AYVV-[PD] genome of both polarity was observed and verified. Replication-associated (Rep) protein of AYVV-[PD] was detected only in bacteria generating the corresponding sscDNAs, whereas disruption of the Rep gene abolished the phenomenon. The results suggested that a single copy of ori is sufficient for the prokaryotes to support the generation of unit-length, genomic sscDNAs of begomoviruses, which requires the presence of functional Rep protein.